Sustainable Production of Microbial Lipids from Renewable Biomass: Evaluation of Oleaginous Yeast Cultures for High Yield and Productivity - Lee, Jungeun (Kansas State University, 2017)
Microbial lipids derived from oleaginous yeasts are a promising alternative source of edible oils due to the following advantages: no requirement of broad lands; availability of year-round production; and no food versus fuels controversy. Oleaginous yeast has an inherent ability to accumulate lipids inside cells and their lipids are preferable as starting materials in oleo-chemical industries because of their distinct fatty acid composition. Lignocellulosic biomass is a promising substrate to supply carbon sources for oleaginous yeast to produce lipids due to the high content of polysaccharides and their abundancy. Lignocellulosic-based sugar streams, which can be generated via pretreatment and enzymatic hydrolysis, contained diverse monosaccharides and inhibitors. The major objectives of this study were: 1) to develop a novel purification method to generate clean sugar stream using sorghum stalks after acid pretreatment; 2) to optimize fermentation conditions for Trichosporon oleaginosus to achieve high yields and productivity of microbial lipids using lignocellulosic hydrolysates; 3) to investigate the potentials of sorghum stalks and switchgrass as feedstocks for microbial lipid production using oleaginous yeast strains, such as T. oleaginosus, Lipomyces starkeyi, and Cryptococcus albidus; 4) to develop an integrated process of corn bran based-microbial lipids production using T. oleaginosus; and 5) to develop bioconversion process for high yields of lipids from switchgrass using engineered Escherichia coli. In our investigation, major inhibitory compounds of lignocellulosic hydrolysates induced by pretreatment were acetic acid, formic acid, hydroxymethyl furfural (HMF) and furfural. The activated charcoal was effective in removing hydrophobic compounds from sorghum stalk hydrolysates. Resin mixtures containing cationic exchangers and anionic exchangers in 7:3 ratio at pH 2.7 completely removed HMF, acetic acid, and formic acid from sorghum stalk hydrolysates. T. oleaginosus was a robust yeast strain for lipid production. In the nitrogen-limited synthetic media, total 22 g/L of lipid titers were achieved by T. oleaginosus with a lipid content of 76% (w/w). In addition, T. oleaginosus efficiently produced microbial lipids from lignocellulosic biomass hydrolysates. The highest lipid titers of 13 g/L lipids were achieved by T. oleaginosus using sorghum stalk hydrolysates with a lipid content of 60% (w/w). L. starkeyi and C. albidus also successfully produced microbial lipids using lignocellulosic hydrolysate with a lipid content of 40% (w/w). Furthermore, corn bran was a promising feedstock for microbial lipid production. The highest sugar yields of 0.53 g/g were achieved from corn bran at the pretreatment condition of 1% acid and 5% solid loading. Microbial lipids were successfully produced from corn bran hydrolysates by T. oleaginosus with lipid yields of 216 mg/g. Engineered E. coli also effectively produced lipids using switchgrass as feedstocks. E. coli ML103 pXZ18Z produced a total of 3.3 g/L free fatty acids with a yield of 0.23 g/g. The overall yield of free fatty acids was 0.12 g/g of raw switchgrass and it was 51 % of the maximum theoretical yield. This study provided useful strategies for the development of sustainable bioconversion processes for microbial lipids from renewable biomass and demonstrated the economic viability of a lignocellulosic based-biorefinery.
Keywords: Oleaginous yeast; Microbial lipids; Single cell oil; Lignocellulosic biomass; Fermentation; Pretreatment